Development of Аntarctic protected areas: mathematical forecast for 2020 - Kuzko, O.V.; Fedchuk, A.P.; Savchenko, V.V. (Український антарктичний журнал, 2015)
This paper discusses the growing dynamics of the increasing of the amount and especially the Antarctic Specially Protected Areas (ASPA) and the Antarctic Specially Managed Areas (ASMA). This dynamics is a reflection of the sustainable environmental imperative in the national interests of the Antarctic Treaty Parties. This dynamics is analyzed using the Richardson’s model, which was used by Thomas L. Saaty for the analysis of the arms race dynamics in the twentieth century. Using this model made it possible to estimate the expected of the ASPA and ASMA amount and areas in the near future. So in 2020 it is expected to increase the total areas of ASPA and ASMA up to 103,700 km2 (which is comparable to the Iceland area). The question of the accuracy increasing of the used model and the accuracy of the quantitative characteristics is discussed. The obtained quantitative characteristics will provide the policy makers and national Antarctic program managers by the additional arguments for decision-making on the further management of the human activities and nature conservation in the Antarctic. Among the general public obtained characteristics will contribute to the better understanding of the development trends of the international legal regime of the Antarctic. У статті аналізується динамічне зростання кількості та загальної площі Антарктичних районів, які особливо охороняються (АРОО) та Антарктичних районів, які особливо управляються (АРОУ), що є відображенням стійкого природоохоронного імперативу у спектрі національних інтересів Сторін Договору про Антарктику. Зазначена динаміка проаналізована за допомогою моделі Річардсона, яка була застосована Томасом Сааті для аналізу динаміки гонки озброєнь у ХХ столітті. Використання зазначеної моделі дало змогу спрогнозувати кількість та загальну площу АРОО та АРОУ у найближчому десятилітті. Так, у 2020 році згідно з результатами моделювання очікується, що загальна площа АРОО та АРОУ складатиме 103 700 км2 (співмірно з площею Ісландії). Обговорюється питання підвищення точності моделі, що використовується, і точності отриманих кількісних характеристик. Отримані кількісні характеристики нададуть політикам і керівникам національних антарктичних програм додаткові аргументи для вироблення рішень щодо подальшого управління людською діяльністю та охороною природи в Антарктиці. Серед широкої громадськості отримані кількісні характеристики сприятимуть кращому розумінню тенденцій розвитку міжнародно-правового режиму Антарктики. В статье анализируется возрастающая динамика увеличения количества и общей площади особо охраняемых районов Антарктики (ООРА) и особо управляемых районов Антарктики (ОУРА), что является отражением устойчивого природоохранного императива в спектре национальных интересов Сторон Договора в Антарктике. Указанная динамика анализируется с помощью модели Ричардсона, которая была применена Томасом Саати для анализа динамики гонки вооружений в ХХ столетии. Использование указанной модели дало возможность спрогнозировать количество и площадь ООРА и ОУРА в ближайшем десятилетии. Так, к 2020 г. ожидается, что общая площадь ООРА и ОУРА увеличится и составит 103 700 км2 (что сопоставимо с площадью Исландии). Обсуждается вопрос повышения точности используемой модели и точности полученных количественных характеристик. Полученные количественные характеристики предоставят политикам и руководителям национальных антарктических программ дополнительные аргументы для выработки решений по дальнейшему управлению человеческой деятельностью и по охране окружающей. среды в Антарктике. Среди широкой общественности полученные количественные характеристики будут способствовать лучшему пониманию тенденций развития международно-правового режима Антарктики.